Pain in cognitively impaired children: a focus for general pediatricians. - Massaro, M; Pastore, S; Ventura, A; Barbi, E (Eur J Pediatr, 2013)
UNLABELLED: Pain in children with cognitive impairment and cerebral palsy is a particularly relevant issue due to its high prevalence and impact on quality of life. We review available evidence about prevalence of pain, causes and specific treatment, recognition and use of specific pain scales, physiology, and consequences of pain in this subset of patients. CONCLUSIONS: Pain is very common and is a critical determinant of quality of life in children with cognitive impairment and cerebral palsy. The diseases and associated complications that frequently expose these patients to pain can be treated and pain prevented. For patients with communication difficulties, appropriate, effective, validated tools are available and should be used to diagnose pain in itself, to >choose analgesic treatment and to determine effectiveness of these therapies. The level of awareness of pediatricians towards this issue seems to be quite low.
Keywords: Analgesics; Cerebral Palsy; Child; Cognition Disorders; Humans; Pain; Pain Measurement; Quality of Life